Keterampilan Berbicara Bahasa Arab - Samsir, Nurul Fajriani; Hasmawati, Hasmawati; Bachtiar, Fauziah (Academic : Journal of Social and Educational Studies, 2025)
Abstract. This research is a qualitative descriptive study aimed at obtaining data on the level of Arabic-speaking skills of students. Data collection was conducted through oral tests. The population in this study consisted of 16 ninth-grade students of SMP Al-Bayan Putri Makassar, and the sample was determined using a total sampling technique. Based on data analysis, the results showed that the Arabic-speaking skills of ninth-grade students at SMP Al-Bayan Putri Makassar were 66.40%, categorized as moderateKeywords: Language Skills, Speaking, Arabic Language